Dampak Pencemaran Laut Terhadap Keberlanjutan Sumber Daya Ikan Demersal - Risman (CV. SINAR HOWUHOWU, 2025)
Marine pollution is one of the major threats to the sustainability of fisheries resources, particularly demersal fish that inhabit the seabed. This study aims to analyze the relationship between the level of marine pollution and the sustainability of demersal fish in the coastal waters of X Regency, Y Province. A descriptive quantitative approach was used, involving primary data collection through water and sediment sampling, fish catch monitoring, and secondary data from related institutions. Laboratory analysis revealed that concentrations of heavy metals such as Hg, Pb, and Cd in several locations exceeded the marine environmental quality standards. A decline in dissolved oxygen (DO) levels and elevated total suspended solids (TSS) further worsened the condition of the benthic habitat. Catch data from local fishermen showed a consistent decline in both the quantity and size of demersal fish over the past five years. Correlation analysis indicated a significant negative relationship between pollution levels and fish catch. Spatial disparities were also observed, with areas farther from pollution sources showing better resource potential. These findings suggest that marine pollution directly affects both ecosystems and the socio-economic conditions of coastal communities. Therefore, integrated efforts are needed to control pollution and protect benthic habitats to ensure the sustainability of demersal fish resources.